A novel approach to ductal spasm during percutaneous device occlusion of patent ductus arteriosus. (22nd December 2015) - De Decker, Rik; Comitis, George; Thomas, Jenny; van der Merwe, Elmarie; Lawrenson, John
Abstract: Ductal spasm is a rare yet important complication of device occlusions of patent ductus arteriosus. Spasm may result in failure of the procedure, under-sizing of the device, or embolisation of the implanted device as the spasm resolves after the procedure. We describe a novel protocol that rapidly and completely reversed the spasm in eight prematurely born infants who experienced ductal spasm during cardiac catheterisations for patent ductus arteriosus occlusion. In total, eight infants born between 25 and 34 weeks of gestation presented for transcatheter patent ductus arteriosus occlusion between 13 and 87 months of age. All eight patients experienced ductal spasm either immediately before, during, or soon after induction of anaesthesia or only after entering the ductus arteriosus with a catheter. After detection of the spasm, the anaesthetist, in each case, changed the mode of anaesthesia from inhaled sevoflurane to total intravenous anaesthesia with propofol, reduced the inhaled oxygen fraction to 21%, and initiated a continuous intravenous infusion of prostaglandin E1 . The first two steps (total intravenous anaesthesia and FiO2 0.21) resulted in only partial relaxation of the spasm. Complete relaxation was attained after intravenous prostaglandin E1 infusions of only 10–15 minutes' duration. While maintaining this protocol, six ducti were successfully occluded and two were considered to be unsuitable for device occlusion and were referred for surgery. Ductal spasm during transcatheter occlusion may be reliably resolved and the procedure safely completed by a simple anaesthetic protocol, including the continuous infusion of intravenous prostaglandin E1 .